Elaboración de un publirreportaje para difundir los valores culturales de la imagen del señor del árbol de la provincia de Cotopaxi, cantón Saquisilí sector Cuicuno en el año 2016 - Lema Rubio, Luis Alberto (2016)
Through the development of the Advertorial we could gather information about the cultural values of the image of the “Señor del Arbol”, Cuicuno, Parish of Saquisilí of Cotopaxi Province, in 2016, raising awareness in the community and its surroundings the importance that the image has in the pilgrims, to be a clear dissemination relating to the values that the image has from its ancestors, it was necessary to implement the field research, which facilitated the collection of information concerning the legends of the image, they were taken from two books, one of them is in the possession of Mrs. Zarzosa and the other is with Mr. Juan Maria Defaz, residents of Cuicuno therefore they have not been widespread among tourists who visit the sanctuary. Various field research tools were used to collect actual data that exist in the area; interviews and surveys provided information to develop the Advertorial of the image of the “Señor del Arbol”of Cuicuno with potential characteristics of people who practice cultural values, whereby the following results were obtained, 40% of residents and tourists know the image, but they are unaware of its legends regarding the appearance of it, for that reason they accepted the proposal that was made with the contributions from residents and tourists who come to Cuicuno.